Raspberry Pi Technology - Cox, Simon; Johnston, Steven (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The Raspberry Pi Foundation aims to promote the teaching of Computer Science and released the first Raspberry Pi device in February 2012. It is often referred to as a Single Board Computer (SBC), meaning that it runs a full operating system and has sufficient peripherals to start execution without additional hardware. Although other Single Board Computers (SBC) existed before, the Raspberry Pi Foundation made the SBC accessible to almost anyone, introducing not just a low-cost computer, but one that can bridge the gap to the physical world via standard electronic interfaces; controlled programmatically from the operating system. This has led to the popularity of the Raspberry Pi, not only in education but with industry, hobbyists, prototype builders, gamers and the curious, and it has enabled people to experiment in new ways. In this book, we show how the Raspberry Pi is being used for specific research prototypes; to construct testbeds; applied to Internet of Things applications, as well as educational contexts.